2015
DOI: 10.1007/s11104-015-2622-2
|View full text |Cite
|
Sign up to set email alerts
|

Native plants and nitrogen in agricultural landscapes of New Zealand

Abstract: Native vegetation of the Canterbury Plains of South Island in New Zealand has been heavily modified by agriculture and now occupies less than 0.5% of the total land area. With recent large-scale conversion to intensive dairy farming, restoration of native plants and biodiversity into a modern agricultural matrix creates a significant challenge. Native species are adapted to low nitrogen (N) environments but fertilizers and effluents have substantially raised soil N loadings. We investigated the interactions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 43 publications
2
29
1
Order By: Relevance
“…; Marden & Phillips ), as well as studies of plant N uptake and influence on rhizosphere soil (Franklin ; Franklin et al . ). Comparative data for growth rate, root density and depth were largely from plants excavated and measured after 5 years growth in alluvial soil (Marden et al .…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…; Marden & Phillips ), as well as studies of plant N uptake and influence on rhizosphere soil (Franklin ; Franklin et al . ). Comparative data for growth rate, root density and depth were largely from plants excavated and measured after 5 years growth in alluvial soil (Marden et al .…”
Section: Methodsmentioning
confidence: 97%
“…; Franklin et al . ). Nitrogen content is an important factor influencing litter decomposition by soil microbes; leaves with high N content (low C:N and lignin:N ratios) tend to decompose faster returning more N to the soil (Table , Box 1; Cornwell et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nutrient spillover has been shown to negatively impact and threaten the sustainability of fragments of native vegetation adjacent to farms ( Didham et al, ; Bowie et al, ). Native species appear to be tolerant of, but not particularly responsive to, elevated soil loadings of N and P. We have found that native plants assimilate large amounts of applied N into foliage as luxury uptake which may be an adaptation of native species to naturally low fertility soils ( Franklin et al, ). Aside from this research, we have little understanding of the compatibility of fertile soils for establishing and sustaining native vegetation in New Zealand.…”
Section: Introductionmentioning
confidence: 96%
“…The rate of denitrification and the relative proportions for NO, N 2 O, and N 2 produced depend on the complex interactions between soil properties, soil microorganisms, climatic factors and management practices (Bieganowski et al, 2013;Franklin et al, 2015;Liu et al, 2010;Stępniewski and Stępniewska, 2009;Włodarczyk et al, 2014). From an environmental perspective, a very important result is the N 2 O/N 2 +N 2 O ratio, which shows the N 2 O-reducing activity of soil (Yanai et al, 2008).…”
Section: Introductionmentioning
confidence: 99%